Distribution and loss of water and nitrate under alternate and conventional furrow fertigation - Ebrahimian, H.; Liaghat, A.; Parsinejad, M.; Playán, E. (Spanish Journal of Agricultural Research, 2012)
Alternate furrow irrigation and surface fertigation have been known as techniques to control water and fertilizer losses. The main goal of this field study was to characterize the combined effect of these techniques on water and nitrate losses and on soil water and nitrate concentration. Two types of alternate furrow irrigation, i.e., variable alternate furrow irrigation (AFI) and fixed alternate furrow irrigation (FFI), as well as conventional furrow irrigation (CFI) were considered in the experiments. Results evidenced higher infiltration at irrigated furrows under AFI and FFI as compared to CFI. Increased lateral water movement under alternate irrigation resulted in lower water and nitrate losses via runoff and deep percolation. Water application efficiency for the CFI, FFI and AFI strategies amounted to 61.3%, 71.8% and 77.0% in the first fertigation and 36.4%, 58.8% and 60.7% in the second fertigation, respectively. Nitrate runoff for the CFI, FFI and AFI strategies amounted to 32.4%, 31.2% and 25.7% in the first fertigation and 44.3%, 35.1% and 32.7% in the second fertigation, respectively. Soil water content and nitrate concentration at the upstream part of the experimental field were larger than at the middle and downstream parts for all three irrigation regimes. Overall, alternate furrow fertigation, particularly AFI, stands as a simple and practical management practice for water and fertilizer conservation in agricultural fields.